Day-of-the-week returns and mood: an exterior template approach - Shlomo Zilca (Financial Innovation, 2017)
Rule- and template-based pattern-recognition methods are alternative ways to identify various patterns in stock prices alongside more traditional econometric tools. In this study, we generate an exterior template of mood scores from two perplexingly similar samples of mood scores 50 years apart. The mood scores template enables us to deploy a direct test of the behavioral explanation for the day-of-the-week effect. Our evidence shows that the day-of-the-week mood template is a potentially valid explanation of the day-of-the-week effect. Subperiod analysis suggests that the magnitude of the day-of-the-week effect has declined over time. That decline, however, is not uniform across size deciles and is more pronounced in larger capitalization deciles. There is no decline though in the ability of mood to explain the day-of-the-week effect.
Keywords: 650; Pattern recognition; Template; Day-of-the-week effect; Monday effect; Behavioral finance